RADIOLOGICAL SAFETY INDICATORS OF SOIL-GRUNTS DISTRIBUTED ON THE DRYING BOTTOM OF THE ARAL SEA (Scientific journal of the Fergana State University, 2025)
In the article, in the study of the physical chemical biological properties of soil, in the creation of a scientific basis for the selection and grouping of plant species according to the salinity of the soil-soil in the dry bottom of the Aral Sea, the radiological safety of the soil distributed in the dry bottom of the Aral Sea indicators have been studied.